Risk categorization and decision prioritization for climate change impacts: A rapid risk assessment methodology applied in the State of Qatar - Logan Cochrane (7822049) (2023)
The impacts of climate change vary by location and severity, will be experienced over a range of timescales, and governments are not equally able to respond to risks and hazards in the same way. Yet, despite the rapid expansion of climate-related evidence, few studies categorize risks and hazards to support better-informed decision-making regarding the prioritization of action and investment. This paper develops a risk categorization tool and decision support heuristic, applied to the specific challenges faced in the Gulf Cooperation Council (GCC) region, and specifically in the State of Qatar. Drawing on expert assessment, the results of this study allow decision-makers to compare risks and hazards when making decisions about resource allocation and policy interventions. The results represent a localized categorization of climate risks and a comparative assessment based on three criteria. Standardized global assessments were used to validate the results. While the application of this study is specific to one country, the methodology and assessment approach could be applied in other contexts to enable more evidence-informed decision-making. Other Information Published in: Environmental Advances License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.envadv.2023.100429